RESPON DAN ALASAN PETANI TEMBAKAU MENANAM KOMODITAS TANAMAN ALTERNATIF (KEDELAI) DI DESA KEDUNGWARAS KECAMATAN MODO KABUPATEN LAMONGAN - Sholikhah, Siti Zumrotus; Waliulu, Rachman; Sudiyarto, Sudiyarto (Berkala Ilmiah AGRIDEVINA, 2017)
Tobacco has important role in national economic as labour field, income source andfarmer income. But, tobacco business depend on climate change so it has influencedfarmer to plant alternative commodity such as Soya. This research aimed to analysistobacco farmer’s respon to alternative commodity planting, to analysis farmer argumentswho still planting tobacco and  farmer arguments who planting alternative commodity, toanalysis cost and revenue difference between tobacco and soya farm, to analysis farmerarguments which prefer tobacco farm to soya farm. This research held in KedungwarasVillage, Modo Distrisct, Lamongan Regency. Primary and secondary data was analysedby descriptive analysis and statistic analysis. The result showed that farmer respon todefence tobacco farm was good (50% farmer still planting tobacco),while 75 % farmerchange to soya farm. Farmer arguments in defence tobacco farm which have high scorewas follow their parents (43,75%) and farmer arguments in change to soya farm whichhave high score was the success of planting soya. The difference of average productioncost between tobacco and soya was Rp 13.215.302/ha and the difference of averagerevenue was Rp 335521/ha.